Technical advances and stability analysis in wind-penetrated power generation systems—A review - Yadav, V. Vishnuvardhan; Saravanan, B. (Frontiers in Energy Research, 2022)
Recently, wind power from renewable energy power generation has been extended quickly to another level. To the grid, most renewable generators synchronize through the power electronic converters controlled flexibly. The high-level wind power penetration into the power generation system affects the dynamic performance of the power system and presents substantial uncertainties in system operation. This study mainly focuses on reviewing the various types of stability analyses in high-level wind penetration of power generation systems. It describes several challenges and simulation analyses related to stability issues. A comparative analysis has also been carried out for the various types of stability related to different research studies. The data show that transient stability has been significantly focused on in most of the studies.